2022
DOI: 10.3390/genes13071109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19-Associated DNA Methylation Variations by Integrating Methylation Array and scRNA-Seq Data at Cell-Type Resolution

Abstract: Single-cell transcriptome studies have revealed immune dysfunction in COVID-19 patients, including lymphopenia, T cell exhaustion, and increased levels of pro-inflammatory cytokines, while DNA methylation plays an important role in the regulation of immune response and inflammatory response. The specific cell types of immune responses regulated by DNA methylation in COVID-19 patients will be better understood by exploring the COVID-19 DNA methylation variation at the cell-type level. Here, we developed an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The tumor necrosis factor receptor-related factor 3 (TRAF3) interacting protein 3 (TRAF3IP3) plays an essential role in both the innate and adaptive immunity. Several genomic and methylation studies on COVID-19 have found that TRAF3IP3 can serve as a potential epigenetic biomarker for COVID-19 and is a key mutated region in severe patients, compared with non-severe COVID-19 patients [ 49 , 50 ]. The protein encoded by CD48 is present on the surface of many immune cells and endothelial cells, and is involved in the activation and differentiation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor necrosis factor receptor-related factor 3 (TRAF3) interacting protein 3 (TRAF3IP3) plays an essential role in both the innate and adaptive immunity. Several genomic and methylation studies on COVID-19 have found that TRAF3IP3 can serve as a potential epigenetic biomarker for COVID-19 and is a key mutated region in severe patients, compared with non-severe COVID-19 patients [ 49 , 50 ]. The protein encoded by CD48 is present on the surface of many immune cells and endothelial cells, and is involved in the activation and differentiation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Significant cell-type specific DNA hypermethylation lowering the expression of gamma-delta T cells immune and virus-related signaling pathways genes ) S100A9, AHNAK, CX3CR1, TRAF3IP3 , and LFNG ) in COVID-19 patients (Wang et al, 2022).…”
Section: Genome-wide Dna Methylation Alterations Associated With Covi...mentioning
confidence: 96%